Nouvelle rhétorique et formation du citoyen : perspectives sur l’enseignement du discours à partir d’une université d’été - Lucie Donckier de Donceel; Benjamin Sevestre-Giraud (Argumentation et Analyse du Discours, 2023)
Even though it is now clearly established that the rhetorical education model provides a relevant framework to question the methods and contents of a democratic citizenship education, this model still encounters difficulties in Europe for recognition as a valid pedagogical approach for working on critical thinking and citizenship skills. Based on the experience of a summer school entitled “European Citizenship and Rhetorical argumentation: the case of climate change”, we will try to answer the criticisms addressed to rhetoric and show how it can be used to develop citizenship skills nowadays.